Analysis of Factors Affecting Audit Quality at the North Sumatra Financial and Development Supervisory Agency - Jhon Piter; Rini Indahwati; Enda Noviyanti Simorangkir (Journal of Research in Business, Economics, and Education, 2020)
Researchers took the object of research at the North Sumatra Financial and Development Supervisory Agency (BPKP), the choice of objects was due to improving audit quality. The theories used in this research are theories about audit quality and its measurement. The population in this study were 150 auditors who worked at BPKP North Sumatra. The data collection method used was the survey method. The population used with the Slovin formula is 110 auditors and the sample size used is 30 auditors. The results of hypothesis testing in this study indicate that the variables of time budget pressure, auditor experience and understanding of information systems partially affect audit quality, while audit complexity and accountability variables have no effect on audit quality. Simultaneously, audit complexity, time budget pressure, auditor experience, accountability, and understanding of information systems affect audit quality. Based on the research results, audit complexity, time budget pressure, auditor experience, accountability and understanding of information systems have an effect on audit quality.